Development of STEAM-ESD-oriented Renewable Energy Learning Tools to improve creative thinking and environmental literacy - Nur Hikmah; Ary Susatyo Nugroho; Siti Patonah (Jurnal Penelitian Pembelajaran Fisika, 2025)
Renewable energy education empowers students to become creative and innovative agents of change in efforts to protect the environment. This study aims to determine the characteristics, validity, practicality, and effectiveness of learning tools on the topic of renewable energy oriented towards Science, Technology, Engineering, Art, and Mathematics (STEAM) - Education for Sustainable Development (ESD) to improve creative thinking and environmental literacy skills. The research was conducted in two different classes using a research and development (R&D) approach. The ADDIE model (Analyze, Design, Development, Implementation, and Evaluation) was used with stages of needs analysis and mini-research, device design and evaluation, as well as development, implementation, and results. The data collection methods used were interviews, tests, and questionnaires. Based on expert validation results, the category obtained was very feasible to use with an average validation of ATP 89%, Teaching Module 88%, Teaching Materials 87.10%, LKPD 94%, and Creative Thinking Instruments 85.25%. The research results showed an average practicality score of 96% in the very practical category. Meanwhile, the improvement in creative thinking skills and environmental literacy was quite effective.